The Cambridge handbook of stakeholder theory - Harrison, Jeffrey S.; Barney, Jay B.; Freeman, R. Edward, 1951-; Phillips, Robert A. (Cambridge : Cambridge University Press, 2019)
In the decades since R. Edward Freeman first introduced stakeholder theory, which views firms in terms of their relationships to a broad set of partners, the stakeholder approach has drawn increasing attention as a model for ethical business. Edited by Freeman, alongside other leading scholars in stakeholder theory and strategic management, this handbook provides a comprehensive foundation for study in the field, with eighteen chapters covering some of the most important topics in stakeholder theory written by respected and highly cited experts. The chapters contain an overview of the topic, an examination of the most important research on the topic to date, an evaluation of that research, and suggestions for future directions. Given the pace of new scholarship in the field, this handbook will provide an essential reference on both foundational topics as well as new applications of stakeholder theory to entrepreneurship, sustainable business, corporate responsibility, and beyond.
Title from publisher's bibliographic system (viewed on 09 May 2019).
Keywords: Management; Organizational sociology; Corporate governance